English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I am graphing quadratic equations. The value of x is given.
The value of x is -3.
The equation is y=-x^2-2x
My question is: since the x in the equation is already negitve and when squared is positive than would the value of the original x stay -3.It is like three negitive signs in a row.

2006-10-31 08:13:19 · 5 answers · asked by Neil 1 in Science & Mathematics Mathematics

5 answers

That is correct. You have an upside down parabola...

f(x) = -x^2 - 2x
f(-3) = -(-3)^2 - 2(-3)
f(-3) = -9 - (-6)
f(-3) = -9 + 6
f(-3) = -3

So for x = -3, y = -3

2006-10-31 08:15:27 · answer #1 · answered by Puzzling 7 · 0 0

if y=x^2-2x then for x=-3 you get:

y = (-3)(-3) -(2)(-3)
= +9 +6
= +15

2006-10-31 16:29:17 · answer #2 · answered by jonathon.shine@rogers.com 2 · 0 0

there is a point on the parabola at (-3, -3).

PEMDAS. -(-3)^2 = -9
-9--6 = -3

2006-10-31 16:29:45 · answer #3 · answered by davidosterberg1 6 · 0 0

y=(-3)^2-2(-3)=9+6=15

does this help? I'm not qyite sure what you are asking.

2006-10-31 16:17:41 · answer #4 · answered by yupchagee 7 · 0 0

y=x^2 -2x

y=(-3)(-3) + -2(-3)

y= 9 + 6

y=15

2006-10-31 17:29:29 · answer #5 · answered by mom 7 · 0 0

fedest.com, questions and answers